Varietal responses of root characteristics to low nitrogen application explain the differing nitrogen uptake and grain yield in two rice varieties - Liu, Lei; Cui, Kehui; Qi, Xiaoli; Wu, Yu; Huang, Jianliang; Peng, Shaobing (Frontiers in Plant Science, 2023)
To understand the relationship of root plastic responses with nitrogen uptake when reducing nitrogen application for green rice production, a hydroponic experiment and a soil pot experiment were conducted under high (HN) and low (LN) nitrogen applications, using two rice (Oryza sativa L.) varieties, NK57 and YD6, three nitrogen absorption traits (total nitrogen accumulation, net NH4 + influx on root surface, nitrogen uptake via apoplasmic pathway) and root characteristics were investigated. In comparison with HN, LN significantly reduced nitrogen absorption and grain yield in both varieties. Concomitantly, there was a decrease in total root length, root surface area, root number, root volume, and root cortical area under LN, while single root length, root aerenchyma area, and root lignin content increased. The expression of OsAMT1;1 and OsAMT1;2 down-regulated in both varieties. The findings revealed that YD6 had smaller reduction degree for the three nitrogen absorption traits and grain yield, accompanied by smaller reduction degree in total root length, root surface area, root cortical area, and expression of the two genes under LN.